PEMBIBITAN SECARA STEK-MINI TANAMAN MELATI [Jasminum sambac (L.) Aiton] - Handayani, Titin (Jurnal Sains dan Teknologi Indonesia, 2006)
The experiment aimed at maximizing the speed growth and number of plants obtained by the mini-steck of jasmine (Jasminum sambac (L.) Aiton) cv. Emprit. Changes in benzylaminopurine (BAP), indolebutiric acid (IBA), and “rooton” concentration.were evaluated. Branchs were used as the plant material source, which consisted of axillary buds obtained after careful excision of the leaves. The following treatments were tested: solid media (soil : sand = 1 : 1) with different BAP concentrations (0.1, 3 and 5 mg/kg), IBA (0, 100, 200 and 300 ppm/kg), and “rooton” (0, 100, 200 and 300 ppm/kg) The results showed that shoots growth slowly in the media suplemented with BAP, however, IBA 200 ppm/kg media is better. Rooton with 300 ppm/kg media showed best results for rooting induction.